Arrestin Expression in E. coli and Purification. Issue 1 (1st December 2014) - Vishnivetskiy, Sergey A.; Zhan, Xuanzhi; Chen, Qiuyan; Iverson, Tina M.; Gurevich, Vsevolod V.
Abstract: Purified arrestin proteins are necessary for biochemical, biophysical, and crystallographic studies of these versatile regulators of cell signaling. Described herein is a basic protocol for arrestin expression in E. coli and purification of the tag‐free wild‐type and mutant arrestins. The method includes ammonium sulfate precipitation of arrestins from cell lysates, followed by heparin‐Sepharose chromatography. Depending on the arrestin type and/or mutations, the next step is Q‐Sepharose or SP‐Sepharose chromatography. In many cases the nonbinding column is used as a filter to bind contaminants without retaining arrestin. In some cases both chromatographic steps must be performed sequentially to achieve high purity. Purified arrestins can be concentrated up to 10 mg/ml, remain fully functional, and withstand several cycles of freezing and thawing, provided that overall salt concentration is maintained at or above physiological levels. © 2014 by John Wiley & Sons, Inc.